Optimasi Konsentrasi Ekstrak Kayu Secang dan Campuran Pasir Kuarsa dengan Kulit Kerang yang Digunakan pada Pembuatan Kompon Karet - Rahmaniar Rahmaniar; Amin Rejo; Gatot Priyanto; Basuni Hamzah (agriTECH, 2016)
This study aimed to obtain the optimum concentration of Sappan Wood Extract, Quartz Sand and Clamshell mixture. For this purpose, Response Surface Methodology (RSM) was used to optimize the factors which influenced the quality of rubber compound. There were two factors to be observed in this study. They were the concentration of Sappan ood Extract (8 phr, 9 phr and 10 phr) and the mixture Quartz Sand and Clamshell (63:37, 73:27 and 83:17). The observed parameters were the hardness, the tensile strength and the elongation at break. The results of the study showed that the optimum hardness was reached at the treatment combination of 8.55 phr for the Sappan Wood Extract and 77.7:22.3 for the mixture of Quartz Sand and Clamshell mixture. Furthermore, the optimum tensile strenght was obtained at the treatment combination of 8.48 phr for the Sappan Wood Extract and 60.3:39.7 for the mixture of quartz sand and seashell. Finally, the optimum elongation at break was reached at the treatment combinatioan of 9,55 phr for the sappan wood extract and 70.65:29.35 for the mixture of of quartz sand and clamshell. Based on these three parameters, the optimum usage of sappan wood extract, quartz sand and clamshell mixture in the making of rubber compound was reached in the proportion of 8.48 phr–9.55 phr for the sappan wood extract, and 60:39.7; 77.7:22.3 for the mixture of quartz sand and clamshell.ABSTRAKPenelitian ini bertujuan untuk mendapatkan konsentrasi ekstrak kayu secang dan campuran pasir kuarsa dan kulit kerang yang optimum. Metode Respon Surface Methodology (RSM) digunakan untuk mengoptimalkan faktor-faktor yang berpengaruh terhadap mutu kompon karet. Dua faktor yang diteliti terdiri dari konsentrasi ekstrak kayu secang (8, 9 dan 10 phr) dan campuran pasir kuarsa dan kulit kerang (63:37, 73:27 dan 83:17). Parameter yang diamati adalah kekerasan, tegangan putus dan perpanjangan putus. Hasil penelitian menunjukkan kekerasan yang optimum dicapai pada kombinasi perlakuan ekstrak kayu secang dan campuran silika pasir kuarsa dan kulit kerang 8,55phr dan 77,7:22,3. Tegangan putus yang optimum dicapai pada kombinasi perlakuan ekstrak kayu secang dan campuran pasir kuarsa dan kulit kerang 8,48 phr dan 60,3:39,7, sedangkan parameter perpanjangan putus yang optimum dicapai pada kombinasi perlakuan ekstrak kayu secang dan campuran pasir kuarsa dan kulit kerang 9,55 phr dan 70,65:29,35, sehingga kondisi optimum penggunaan konsentrasi ekstrak kayu secang dan campuran pasir kuarsa dan kulit kerang pada pembuatan kompon karet berdasarkan ke tiga parameter tersebut dicapai dengan proporsi ekstrak kayu secang dan campuran pasir kuarsa dan kulit kerang optimum 8,48-9,55 phr dan 60:39,7; 77,7:22,3 phr.